ISLAMIC TOURISM AS A STRATEGIC COMPONENT OF THE SHARIA ECONOMY: A SYSTEMATIC LITERATURE REVIEW - Citra Dhistia Murti (PT. Samudra Solusi Profesional, 2025)
Islamic tourism has emerged as a significant segment within the global tourism industry, particularly in countries with Muslim-majority populations and regions seeking to tap into the growing Muslim travel market. This study aims to systematically review and synthesize existing literature on Islamic tourism as an integral component of the sharia economy, focusing on its conceptual foundations, development patterns, economic implications, and governance challenges. Employing a qualitative systematic literature review approach, this article analyzes peer-reviewed journal articles, institutional reports, and policy documents published between 2010 and 2024. The review is guided by predefined inclusion criteria, emphasizing scholarly works indexed in reputable databases and official statistical sources. The findings indicate that Islamic tourism is not merely a niche market but a comprehensive economic ecosystem encompassing halal hospitality, sharia - compliant financial services, cultural preservation, and ethical consumption. Several studies highlight the role of Islamic tourism in enhancing economic inclusivity, strengthening local micro-enterprises, and supporting sustainable development goals. However, the literature also reveals persistent challenges, including conceptual ambiguities, regulatory fragmentation, inconsistent standards of halal certification, and limited integration between tourism stakeholders and Islamic financial institutions. Empirical evidence from international tourism reports and national statistical agencies, including Indonesia’s Central Bureau of Statistics (BPS), demonstrates the growing contribution of Muslim-friendly tourism to national economies. Despite this potential, the implementation of Islamic tourism remains uneven across regions due to institutional, infrastructural, and policy constraints. This study contributes to the literature by offering a structured conceptual framework that positions Islamic tourism within the broader sharia economic system. It also identifies research gaps and proposes future research directions to strengthen theoretical development and policy formulation. The article is expected to provide valuable insights for academics, policymakers, and practitioners seeking to develop Islamic tourism as a sustainable economic strategy.